Genome-Wide Identification and Characterization of GASA Gene Family in Nicotiana tabacum - Li, Zhaowu; Gao, Junping; Wang, Genhong; Wang, Shuaibin; Chen, Kai; Pu, Wenxuan; Wang, Yaofu; Xia, Qingyou; Fan, Xiaorong (Frontiers in Genetics, 2022)
The gibberellic acid stimulated Arabidopsis (GASA) gene family is critical for plant growth, development, and stress response and has been studied in various plant species; however, the roles of GASA in tobacco (Nicotiana tabacum) are unexplored. In this study, we identified 18 GASA in the tobacco genome (NtGASA) distributed to 13 chromosomes. All the proteins contained a conserved GASA domain and a highly specific 12-cysteine residue at the C-terminus. Phylogenetic analysis divided NtGASA into three well-conserved subfamilies, whereas synteny analysis suggested that tandem and segmental duplications played an important role in the expansion of the gene family. Analysis of cis-elements showed that NtGASA might influence different phytohormone and stress responses, whereas tissue expression analysis revealed unique or distinct expression patterns in different tissues, suggesting the potential involvement of NtGASA in plant growth and development. We also found that NtGASA expression was mostly regulated by abscisic and gibberellic acid, signifying its role in the two phytohormone signaling pathways. Overall, our findings helped characterize NtGASA and provided useful information for further studies on their molecular functions.